Selective HDAC8 Inhibition Attenuates Isoproterenol-Induced Cardiac Hypertrophy and Fibrosis via p38 MAPK Pathway - Zhao, Tingwei; Kee, Hae Jin; Bai, Liyan; Kim, Moon-Ki; Kee, Seung-Jung; Jeong, Myung Ho (Frontiers in Pharmacology, 2021)
Histone deacetylase (HDAC) expression and enzymatic activity are dysregulated in cardiovascular diseases. Among Class I HDACs, HDAC2 has been reported to play a key role in cardiac hypertrophy; however, the exact function of HDAC8 remains unknown. Here we investigated the role of HDAC8 in cardiac hypertrophy and fibrosis using the isoproterenol-induced cardiac hypertrophy model system. Isoproterenol-infused mice were injected with the HDAC8 selective inhibitor PCI34051 (30 mg·kg-1 body weight). Enlarged hearts were assessed by HW/BW ratio, cross-sectional area, and echocardiography. RT-PCR, western blotting, histological analysis, and cell size measurements were performed. To elucidate the role of HDAC8 in cardiac hypertrophy, HDAC8 knockdown and HDAC8 overexpression were also used. Isoproterenol induced HDAC8 mRNA and protein expression in mice and H9c2 cells, while PCI34051 treatment decreased cardiac hypertrophy in isoproterenol-treated mice and H9c2 cells. PCI34051 treatment also reduced the expression of cardiac hypertrophic markers (Nppa, Nppb, and Myh7), transcription factors (Sp1, Gata4, and Gata6), and fibrosis markers (collagen type I, fibronectin, and Ctgf) in isoproterenol-treated mice. HDAC8 overexpression stimulated cardiac hypertrophy in cells, whereas HDAC8 knockdown reversed those effects. HDAC8 selective inhibitor and HDAC8 knockdown reduced the isoproterenol-induced activation of p38 MAPK, whereas HDAC8 overexpression promoted p38 MAPK phosphorylation. Furthermore, p38 MAPK inhibitor SB203580 significantly decreased the levels of p38 MAPK phosphorylation, as well as ANP and BNP protein expression, induced by HDAC8 overexpression. Here we show that inhibition of HDAC8 activity or expression suppresses cardiac hypertrophy and fibrosis. These findings suggest that HDAC8 could be a promising target to treat cardiac hypertrophy and fibrosis by regulating p38 MAPK.